Comparative Efficacy of Antihypertensive Agents in Flow-Mediated Vasodilation of Patients with Hypertension: Network Meta-Analysis of Randomized Controlled Trial - Hong Ding; Shu Liu; Ke-Xin Zhao; Jie Pu; Ya-Fei Xie; Xiao-Wei Zhang (International Journal of Hypertension)
Hypertension induces both structural and functional changes in blood vessels, thereby increasing endothelial dysfunction, which in turn, contributes to an increase in blood pressure. A popular and widely used noninvasive tool, flow-mediated dilation (FMD), is used to examine peripheral artery endothelium-dependent dilation. This study aimed to compare the efficacies of different classes of antihypertensive agents based on their effects on FMD. PubMed, Embase, and Cochrane Library were queried till November 1, 2020. Comparative studies on the efficacies of two or more antihypertensive agents or placebos for hypertensive patients were included. The outcomes were variations in mean systolic and diastolic blood pressure. Two reviewers independently reviewed and filtered the literature and extracted the data; the Cochrane “risk of bias” method was used to evaluate the methodological quality of the randomized controlled trials. A network meta-analysis was performed using Stata 15.0 software with a total of 49 studies. Subgroup analysis based on age and duration of treatments was performed. As compared to the placebo group, patients receiving the antihypertensive drugs exhibited significantly enhanced FMD (ARB + CCB: 4.01%, 95% CI, 0.92–7.11%, p<0.001; ACEI + ARB: 2.81%, 95% CI, 1.19–4.43%, p<0.001; ACEI: 2.55%, 95% CI, 1.34–3.77%, p<0.001; ARB: 2.22%, 95% CI, 1.05–3.38%, p<0.001; β-blocker: 2.23%, 95% CI, 0.93–3.52%, p<0.001). In the SUCRA curve for network meta-analysis, the combination of CCB and ARB was found to be the most effective in increasing FMD (SUCRA = 89.0%), followed by ACEI monotherapy (SUCRA = 74.2%). ARB combined with CCB was superior in improving the endothelial function measured as the FMD; ACEI monotherapy was the most effective treatment among the antihypertension medications. There were no significant differences between antihypertensive drug-based monotherapies.